Evaluating food options in Bangladesh: Analysis of costs, benefits, and tradeoffs between targeted distribution versus public agricultural and infrastructure investments - Dorosh, Paul A.; Thurlow, James; Pradesha, Angga; Raihan, Selim (International Food Policy Research Institute, 2021)
Bangladesh has successfully improved national food security over the last two decades, primarily by increasing rice production and consumption. However, the country’s food system remains vulnerable to periodic floods and droughts that seriously affect agricultural production and prices. While food imports can cushion the effects of these short-term climate shocks, there is always uncertainty about whether shortages in global commodity markets will coincide with domestic production shortfalls, leading to particularly adverse outcomes, especially for poor farmers and net consumers. This is one of the reasons why Bangladesh’s government has maintained a long-standing public grain procurement and storage system, as well as a large social protection program that distributes subsidized rice and wheat to poor households. These programs, together with investments in farm productivity, have enhanced the resilience of Bangladesh’s food system to climate and world market shocks. Heightened climate variability in recent years has also led the government to increase stocks and make substantial new investments to expand public grain storage capacity.